APOLOGIZING STRATEGIES USED IN BARACK OBAMA’S SPEECH AT STRASBOURG TOWN HALL - PRAMUDIA, EKA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Apologizing act, apology strategies, and speechApology is an act that used to restore relationship between addresser and addressee after addresser has offended addressee intentionally or unintentionally. In this study, the writer intends to analyze apologizing strategies used in Barack Obama’s speech at Strasbourg Town Hall. This study is conducted to find out (1) the  types  of  apologizing  strategies  (direct  and  indirect)  performed  in  Barack Obama’s speech, and (2) the apologizing strategies performed in Barack Obama’s speech.This study is qualitative  approach with document analysis since the  data consists largely of words.  The data are the utterances which contain apology in Barack Obama’s speech at Strasbourg Town Hall.  From the data, the writer tried to identify the apologizing strategies by using Olshtain and Cohen’s apologizing strategy (1983).In this study the writer found 8 strategies of apology in the 12 excerpts. The  strategies  are  (a)  IFID  with  exclamations,  (b)  IFID followed  by  humor downgrading, (c)  IFID for politeness,  (d) taking on responsibility followed bysharing guilt, (e) admission followed by blaming, (f) implicit apology followed by regret,  (g)  explanation  or  account,  and  (h)  offer  of  repair.  According  to  theanalysis, the writer finds IFID with exclamations by 1 datum, IFID followed by humor  downgrading  by 1 datum,  IFID for  politeness  by 1 datum,  taking  on responsibility followed by sharing guilt by 4 data, admission followed by blaming by 1 datum,  implicit  apology followed by regret  by 1 datum,  explanation or account by 1 datum,  and offer of repair by 2 data.  The mostly used strategy is taking on responsibility followed by sharing guilt  that  occurred 4 times.  This happens because the speech indicated that  every nation bears responsibility for problems in the world such as climate change, terrorism, drug trafficking, poverty, and the proliferation of nuclear weapons. This strategy was used to minimize the degree of offense that United States is partly responsible.This  study  hopefully  can  provide  appropriate  reference  for  further researcher to conduct the research in apologizing act. It is recommended that the next researchers examine apology strategy used in diplomatic context. Hopefully, the results  of this  study can be used as  the starting point  to analyze apology strategies more deeply.  Finally,  the future researcher may conduct a research on languages other than English.